Effect of Different Ratios of Chicken Meat to Fresh Osyter Mushroom (Pleurotus sajor-caju) on the Physicochemical Properties and Sensory Acceptability of Sausages - Faridah Yahya; Hun Tze Ting (International Journal on Food, Agriculture and Natural Resources, 2020)
This study was aimed to determine the effect of different ratios of chicken meat to fresh oyster mushroom (Pleurotus sajor-caju) on the physicochemical properties and sensory acceptability of chicken sausages. Five formulations of sausages were prepared by different combinations of chicken meat with fresh oyster mushroom (100:0, 85: 15, 70: 30, 55: 45 and 40: 60). The physicochemical analyses included color profile, texture profile, calorie values, and proximate analysis were carried in triplicate while sensory acceptability of chicken sausages were evaluated using sensory acceptance test with 7-point of hedonic scale. Results indicated that the b* value as well as the hardness, springiness, cohesiveness, gumminess, and chewiness of sausages were significantly (p